9y-27=-2y+7

Simple and best practice solution for 9y-27=-2y+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-27=-2y+7 equation:


Simplifying
9y + -27 = -2y + 7

Reorder the terms:
-27 + 9y = -2y + 7

Reorder the terms:
-27 + 9y = 7 + -2y

Solving
-27 + 9y = 7 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-27 + 9y + 2y = 7 + -2y + 2y

Combine like terms: 9y + 2y = 11y
-27 + 11y = 7 + -2y + 2y

Combine like terms: -2y + 2y = 0
-27 + 11y = 7 + 0
-27 + 11y = 7

Add '27' to each side of the equation.
-27 + 27 + 11y = 7 + 27

Combine like terms: -27 + 27 = 0
0 + 11y = 7 + 27
11y = 7 + 27

Combine like terms: 7 + 27 = 34
11y = 34

Divide each side by '11'.
y = 3.090909091

Simplifying
y = 3.090909091

See similar equations:

| 4x+1=3x+11 | | x/3-1/2=1/12 | | 6x+12=3+8x-7 | | 6x+12=3+8x-7 | | 27=-18+9c | | 7x+2=5x-6+8 | | 3(19x+20)=9(7+6x)-1 | | 17x-5=7+15x | | .6w-.4w+.3w=5 | | [k-10]=3 | | 5x+20=6x+8 | | 6(2x-9)+1=6(3x-7)-8(x+2) | | 20=4x+2 | | 2x+3=3x-15 | | 2x+5(2x+1)=7(x-1)-3 | | 2n-10n=40 | | 11x-8-6x=6x-7 | | 1.5x-5=x-4.5 | | 3(7x-8)=4(6x-3) | | 6x+5=-7+2x+20 | | 27=3c+-18+6c | | 7x+20=3x+30 | | 6x+4+15=36 | | 4(6-5x)=3(7-5x) | | [6m]=42 | | 3x+2(x+3)=4(2x-1)-5 | | 6-6x-4=-46+3x-15 | | 4(5x-6)=10x+12x-2x | | 8x+5=4(3x-2)-3 | | 21+1.5h=28-2h | | x^2-3xy+2y^2-y+x=0 | | 11-(2x+5)=-5x+7 |

Equations solver categories